Green Synthesis of Silver Nanoparticles Incorporated Aromatherapies Utilized for Their Antioxidant and Antimicrobial Activities against Some Clinical Bacterial Isolates - Ahmed A. H. Abdellatif; Sultan S. Alhathloul; Abdullah S. M. Aljohani; Hamzah Maswadeh; Emad M. Abdallah; Khalid Hamid Musa; Mohamed A. El Hamd (Bioinorganic Chemistry and Applications)
There is a need to synthesize eco-friendly nanoparticles with more effective and potent antibacterial activities. A green and cost-effective method for the synthesis of silver nanoparticles (AgNPs) using Thymus vulgaris, Mentha piperita, and Zingiber officinale extracts was developed. The analytical instrumentation, namely, UV/Vis, absorption spectroscopy, FTIR, and scanning electron microscopy (SEM), was used to determine the developed AgNPs, confirming the functional groups involved in their reduction. Acidic molybdate, DPPH, and FRAP regents were reacted with AgNPs extract to evaluate their antioxidant, scavenging, and oxidative activities. The agar well diffusion method was used to determine the antibacterial potential of AgNPs extracts using clinical isolates. The developed AgNPs showed peaks at 25 cum\Diff, 50 cum\Diff, and 75 cum\Diff, respectively, of 16.59 ± 0.78, 45.94 ± 1.07, and 81.04 ± 0.98 nm, for Thymus vulgaris, Mentha piperita, and Zingiber officinale. SEM revealed uniform prepared and encapsulated AgNPs by plant extracts matrix. The FTIR shows the involvement of amide (-CO-NH2), carbonyl (-CO), and hydroxyl (-OH), which resulted in the reduction of AgNPs. The AgNPs extract showed significantly higher TAA, DPPH, and FRAP values than free AgNPs and plant extract (p<0.05). Antibacterial of AgNPs extracts revealed various degrees of inhibition zones against Escherichia coli, Acinetobacter baumannii, and Staphylococcus aureus. The developed AgNPs extract showed acceptable antioxidant activities and noticeable antibacterial potential. The prepared green synthesized AgNPs showed a promising antibacterial activity against four multidrug-resistant clinical isolates, Escherichia coli, Acinetobacter baumannii, and Staphylococcus aureus. Further, fractionated extracts other than crude extracts will be utilized in the preparation of AgNPs to get more efficient antibacterial activities for future work.